EFEKTIVITAS STIMULASI KUTAN SLOW STROKE BACK MASSAGE TERHADAP PENURUNAN INTENSITAS NYERI BERSALIN - Fitri, Lidia; Noviawanti, Rice; Sasrawita, Sasrawita (Jurnal Endurance, 2018)
Labor are normal physiological events. Almost 90% of accompanied by pain. Labor consists of four stages: stage I (opening), stage II (fetal expenditure), stage III (discharge uri) and stage IV (observation). Stage I consisting of 2 phases of latent and active phase. Cutaneous stimulation action slow stroke back massage is an intervention done to reduce the pain that occurs during labor. This research to analyze the effectiveness of slow stroke back massage stimulation to decrease the intensity of labor pain the phase I. This research is a quantitative analysis with quasi experiment approach. Population consists of 30 people, sample using Non Random Assignment technique. Analysis is univariat and bivariate, data test is done by parametric statistic using âtâ test to measure pain scale before and after treatment. The average intensity of labor pain before intervention was 6.43 and after intervention was 4.13. The difference between the first and second measurements is 2.3. Result of statistical test got value 0.000 then there is influence of cutaneous stimulation technique slow stroke back massage to decrease intensity of birth pains moment stage I. It is concluded that SSBM is very effective in reducing the intensity of labor pain during the active phase I.Persalinan merupakan kejadian fisiologis yang normal. Hampir 90% persalinan disertai dengan rasa nyeri. Persalinan terdiri atas kala I (pembukaan), kala II (pengeluaran janin), kala III (pengeluaran uri) dan kala IV (observasi). Â Kala I terdiri atas 2 fase yaitu fase laten dan fase aktif. Tindakan stimulasi kutan slow stroke back massage (SSBM) merupakan intervensi yang dilakukan untuk menurunkan rasa nyeri saat persalinan kala I. Tujuan penelitian Â untuk Â menganalisis Â efektivitas Â stimulasi Â kutan slowÂ  strokeÂ  back massage terhadap penurunan intensitas nyeri bersalin kala I.Â  Jenis penelitian Â kuantitatif Â dengan Â pendekatan quasi eksperiment. Populasi berjumlah 30 orang. Sampel dengan teknik Non Random Assignment. Analisis data secara univariat dan bivariat, pengujian data dengan uji statistik t untuk mengukur skala nyeri sebelum dan setelah dilakukan perlakuan. Hasil penelitian menunjukkan rata-rata intensitas nyeri persalinan sebelum intervensi adalah 6.43 dan setelah dilakukan intervensi adalah 4.13. Terlihat nilai mean perbedaan antara pengukuran pertama dan kedua adalah 2.3 dengan standar deviasi 1.393. Hasil uji statistik didapatkan nilai 0.000 maka ada pengaruh teknik stimulasi kutan slow stroke back massage terhadap penurunan intensitas nyeri bersalin kala I. Disimpulkan SSBM sangat efektif dalam menurunkan intensitas nyeri bersalin kala I fase aktif.